The North American Model of Wildlife Conservation - Mahoney, Shane P., 1956-; Geist, Valerius (Book collections on Project MUSE., 2019)
"The foremost experts on the North American Model of Wildlife Conservation come together to discuss its role in the rescue, recovery, and future of our wildlife resources.At the end of the nineteenth century, North America suffered a catastrophic loss of wildlife driven by unbridled resource extraction, market hunting, and unrelenting subsistence killing. This crisis led powerful political forces in the United States and Canada to collaborate in the hopes of reversing the process, not merely halting the extinctions but returning wildlife to abundance. While there was great understanding of how to manage wildlife in Europe, where wildlife management was an old, mature profession, Continental methods depended on social values often unacceptable to North Americans. Even Canada, a loyal colony of England, abandoned wildlife management as practiced in the mother country and joined forces with like-minded Americans to develop a revolutionary system of wildlife conservation. In time, and surviving the close scrutiny and hard ongoing debate of open, democratic societies, this series of conservation practices became known as the North American Model of Wildlife Conservation.In this book, editors Shane P. Mahoney and Valerius Geist, both leading authorities on the North American Model, bring together their expert colleagues to provide a comprehensive overview of the origins, achievements, and shortcomings of this highly successful conservation approach. This volume• reviews the emergence of conservation in late nineteenth-early twentieth century North America• provides detailed explorations of the Model's institutions, principles, laws, and policies• places the Model within ecological, cultural, and socioeconomic contexts• describes the many economic, social, and cultural benefits of wildlife restoration and management• addresses the Model's challenges and limitations while pointing to emerging opportunities for increasing inclusivity and optimizing implementationStudying the North American experience offers insight into how institutionalizing policies and laws while incentivizing citizen engagement can result in a resilient framework for conservation. Written for wildlife professionals, researchers, and students, this book explores the factors that helped fashion an enduring conservation system, one that has not only rescued, recovered, and sustainably utilized wildlife for over a century, but that has also advanced a significant economic driver and a greater scientific understanding of wildlife ecology." --